A study of thermal environment patterns in subway cars and the influence of age on passenger comfort - Qu Wang; Lirong Wu; Yunyang Jiang; Zi'ang Xu (Case Studies in Thermal Engineering)
This study adopts a dual simulation and field research approach to investigate the issue of thermal comfort in subway carriages. The environmental parameters considered in this study are air supply temperature, speed, and humidity. For passengers, variables of age groups and clothing thermal resistance were analyzed. The assessment of the thermal comfort of passengers was conducted using PMV-PPD indexes. The principal findings of this study are as follows: with an increase in air supply speed, the mean temperature in the vicinity of the head and thighs of seated passengers is higher, and the mean temperature in the vicinity of the thighs of standing passengers is greater. When ventilation parameters are altered, the overall degree of change in PMV values is as follows: child passengers > older passengers > adult passengers. To meet established standards, when it is slightly cool (PMV ≈-1), the focus is on the PMV of seated adult passengers to ensure it remains within range. Conversely, when it is slightly warm (PMV ≈-1), the PMV of standing adult passengers is prioritized for the same purpose. These findings offer valuable insights for optimizing subway ventilation systems to improve passenger thermal comfort and guide the development of energy-efficient operations to minimize waste.